The Effect of Sales Volatility, Company Operating Cash Flow Volatility, Accrual Reliability, Book Tax Difference and Market Concentration on Profit Persistency (Case Study on Manufacturing Companies Listed on the IDX for the Period 2021–2023) - Ivana Cahyaningrum; Trisnawati, Rina (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of Sales Volatility, Company Operating Cash Flow Volatility, Accrual Reliability, Book Tax Difference and Market Concentration on Profit Persistence (case study on manufacturing companies listed on the IDX for the period 2021-2023). The type of research used in this study is quantitative research. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023, totaling 233 companies. The sampling technique in this study used the purposive sampling method. The research sample obtained was 132 outliers to 123 manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. This test uses the multiple regression analysis method. The results of this study indicate that the Sales Volatility variable has an effect on profit persistence, while the Company Operating Cash Flow Volatility, Accrual Reliability, Book Tax Difference and Market Concentration have no effect on profit persistence.